Pharaoh's workers - Lesko, Leonard H.; Lesko, Leonard H. (Cornell University Press, 1994)
In one village in western Thebes, villagers worked for centuries on the Egyptian tombs and created timeless beauty. Lesko explores the known facts surrounding their everyday lives and their business partnership with the ruling class of ancient Egypt